Mothers' experience of caring for a child with early onset scoliosis: A qualitative descriptive study. Issue 7 (30th March 2018) - Lauder, Bonnie; Sinclair, Peter M; Maguire, Jane
Abstract : Aims and objectives: This study aimed to identify and describe the experience of parents of children diagnosed with early onset scoliosis living in Australia. Background: Chronic childhood disease has a major impact on health‐related quality of life. Caring for a child with a chronic illness is well documented but the specific experiences of parents who care for children with early onset scoliosis, a rare but devastating illness, has not been explored. Numerous studies have described the interrelated psychological, financial, social, physical and logistical factors that impact the experience of the caregiver role with various diseases, but in the case of early onset scoliosis, limited studies have been conducted about the parental experience. Methods: A qualitative descriptive design was used. A snowball sampling technique assisted in the recruitment. Parents invited to the study included mothers, fathers and guardians. Data were collected through semistructured interviews and transcribed verbatim. Transcripts were analysed thematically. Data collection complied with the Consolidated criteria for reporting qualitative research guidelines. Findings: Twelve mothers of children with early onset scoliosis were interviewed, as only mothers consented to participate. Four major themes emerged: emotional rollercoaster ride, a lack of resources, money talks and pervasive burden . Factors that impacted on the participants' ability to confront, manage and endure caring for a child with early onset scoliosis emerged from the data. Conclusion: The findings suggest there are multiple factors that influence the experience of mothers' caring for a child with early onset scoliosis. The recognition and appropriate management of these factors by healthcare professionals have the potential to improve the quality of life of parents who care for a child with early onset scoliosis. Relevance to clinical practice: Healthcare professionals have first‐line contact with parents of children with early onset scoliosis and are well placed to provide parents with evidence‐based education and increased support.